Development of Interactive E-Modules Based on Heyzine Flipbook on the Potential of Indonesia's Natural Resources in Geography Learning for High School Students - Ady, Wulandari; Astutik, Sri; Nurdin, Elan Artono; Mujib, Muhammad Asyrofula; Susiati, Ana (Universitas Pendidikan Ganesha, 2025)
This research is based on the lack of varied and innovative teaching materials and learning models that are still conventional. This research aims to produce an interactive teaching material product, namely the Heyzine Flipbook Based E-Module. This research is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model developed by Reiser and Mollanda. Data collection instruments used expert validation questionnaires, student response questionnaires and learning outcomes questions. The results of the research carried out obtained values the validity assessment of media experts was 96.8% in the range of 90-100% and the validity level was